Propagation and breaking characteristics of solitons and N-wave in fresh water and brine. Issue 4 (4th July 2017) - Manoj Kumar, G.; Sriram, V.; Schlurmann, T.
ABSTRACT: In this paper, the results of the study on the wave propagation and breaking of solitons and N-waves in fresh water and brine are reported. The experiments were performed in the twin flume facility at the Franzius Institute, Leibniz University of Hannover. Brine from Dead Sea was used for the study. The objective of the experimental study was to determine the flood safety levels along the banks of the Dead Sea and to arrive at the empirical equations for run-up. A weakly coupled numerical model based on the fully nonlinear potential flow and Navier–Stokes equation was used to validate the experimental results. The proposed numerical model is in good agreement with the present experimental results and the available analytical solutions for run-up estimation. The breaking N-waves were found to have a reduced run-up when compared to breaking solitons. The paper shows that the long wave propagation and run-up in both brine and water has similar characteristics.